Venezuelan equine encephalitis vaccine with rearranged genome resists reversion and protects non-human primates from viremia after aerosol challenge. Issue 17 (9th April 2020) - Tretyakova, Irina; Plante, Kenneth S.; Rossi, Shannan L.; Lawrence, William S.; Peel, Jennifer E.; Gudjohnsen, Sif; Wang, Eryu; Mirchandani, Divya; Tibbens, Alexander; Lamichhane, Tek N.; Lukashevich, Igor S.; Comer, Jason E.; et al.
Highlights: Live-attenuated V4020 VEEV vaccine virus contains rearranged structural genes. V4020 includes attenuating mutations from TC83 vaccine engineered to prevent reversions. Next-generation sequencing of V4020 did not detect reversion mutations. V4020-vaccinated macaques were aviremic after stringent aerosol challenge with TrD VEEV. V4020 is a promising experimental vaccine against VEEV. Abstract: Live-attenuated V4020 vaccine for Venezuelan equine encephalitis virus (VEEV) containing attenuating rearrangement of the virus structural genes was evaluated in a non-human primate model for immunogenicity and protective efficacy against aerosol challenge with wild-type VEEV. The genomic RNA of V4020 vaccine virus was encoded in the pMG4020 plasmid under control of the CMV promoter and contained the capsid gene downstream from the glycoprotein genes. It also included attenuating mutations from the VEE TC83 vaccine, with E2-120Arg substitution genetically engineered to prevent reversion mutations. The population of V4020 vaccine virus derived from pMG4020-transfected Vero cells was characterized by next generation sequencing (NGS) and indicated no detectable genetic reversions. Cynomolgus macaques were vaccinated with V4020 vaccine virus. After one or two vaccinations including by intramuscular route, high levels of virus-neutralizing antibodies were confirmed with no viremia or apparent adverse reactions to vaccinations. The protective effect of vaccination was evaluated using an aerosol challenge with VEEV. After challenge, macaques had no detectable viremia, demonstrating a protective effect of vaccination with live V4020 VEEV vaccine.